Adiponectin & Cancer: deep insight. - Dalamaga, M; Koumaki, V (Atlas Genet Cytogenet Oncol Haematol., 2014)
A growing body of evidence suggests that adiponectin presents anti-neoplastic effects via two mechanisms. First, adiponectin can act directly on tumor cells by enhancing receptor-mediated signaling pathways. Secondly, adiponectin may act indirectly by regulating inflammatory responses, influencing cancer angiogenesis and regulating insulin sensitivity at the target tissue site